2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers--Part 2 - Leo C. Polopolus; Fritz Roka; Carol Fountain (EDIS)
This is EDIS document AA253, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. First published February 1992 as Circular 1043 Florida Cooperative Extension Service. Revised November 1997 and December 2002 as Circular 1200.